The Opportunity Development of Urban Tourism Without Gap: Case of Bogor City - Purnomo, Agustina (Politeknik Pariwisata NHI Bandung, 2021)
The development of urban tourism has an opportunity to eliminate the development gap in urban areas, but in contrary almost always giving close access for the substandard urban community. The substandard urban communities are represented by micro-scale tourism providers. This study examines the opportunities provided by the government on micro-scale tourism providers in Bogor City’s tourism development policies. The analysis of three space production activities was arranged by analyzing policy documents and observation. The study found tourism development policies are not sufficient in overcoming gaps in urban tourism development through opportunities given to micro-scale tourism providers. The study suggests tourism development policy has to insert the micro-scale tourism providers as the focus of city tourism development, provide legal access to the city center area, and include them in tourism propaganda.